Lipid-coated nanocrystals of paclitaxel as dry powder for inhalation: Characterization, in-vitro performance, and pharmacokinetic assessment - Kumar M.; Jha A.; Bharti K.; Manjit M.; Kumbhar P.; Dhapte-Pawar V.; Mishra B. (My University, 2025)
Background: Nanocrystals can be produced as a dry powder for inhalation (DPIs) to deliver high doses of drug to the lungs, owing to their high payload and stability to the shear stress of aerosolization force. Furthermore, lipid-coated nanocrystals can be formulated to improve the drug accumulation and retention in lung. Objective: The present work involved the fabrication of paclitaxel nanocrystals using hydrophilic marine biopolymer fucoidan as a stabilizer. Thereafter, fabricated nanocrystals (FPNC) were surface-modified with phospholipid to give lipid-coated nanocrystals (Lipo-NCs). Methods: The nanocrystals were fabricated by antisolvent crystallization followed by the probe sonication. The lipid coating was achieved by thin film hydration followed ultrasonic dispersion technique. Prepared nanocrystals were lyophilized to obtain a dry powder of FPNC and Lipo-NCs, used later for physicochemical, microscopic, and spectroscopic characterization to confirm the successful formation of desired nanocrystals. In-vitro and in-vivo investigations were also conducted to determine the role of nanocrystal powder in pulmonary drug delivery. Results: Lipo-NCs exhibited slower drug release, excellent flow properties, good aerosolization performance, higher drug distribution, and prolonged retention in the lungs compared to FPNC and pure PTX. Conclusion: Lipid-coated nanocrystals can be a novel formulation for the maximum localization of drugs in the lungs, thereby enhancing therapeutic effects and avoiding systemic side effects in lung cancer therapy. © 2024 Elsevier B.V.